The Stability of the Indonesian Sharia Stock Index to Economic Shocks - Faizul Mubarok; Mohammad Nur Rianto Al Arif; Muhammad Arief Mufraini (Ekonomi Syariah IAIN Kudus, 2020)
The stock market has a strategic role in the development of a country's economy in the era of globalization, including the Islamic stock market. The rapid growth of the Islamic stock market, especially in developing countries, is a historical record in Indonesia's financial sector. This study aims to analyze the factors that influence the return of the Indonesian Sharia Stock Index (ISSI) in the short and long term, how long shocks occur, and how much the contribution of these factors. This study uses monthly time series data from January 2012 to December 2019 using the Vector Error Correction Model (VECM) method. VECM estimation results show the price of gold has a significant effect on the short and long term, while inflation has an impact on a long time. ISSI's return quickly reaches stability when it receives a shock from the exchange rate. The price of gold dominates the diversity of ISSI's performances. Stakeholders should consider several things that affect the ISSI return, pay attention to the economic climate, and anticipate quickly the shock that occurs.